Transit ITS Implementation Guidance : Part 2. Transit ITS Projects in China--Lessons Learned - World Bank (Beijing, 2014)
There has been increased interest throughout the world in improving transit services through the introduction of intelligent transportation systems (ITS). ITS can be defined as a set of technologies intended to improve the quality or efficiency of transit services primarily by providing the appropriate information at the appropriate time in an appropriate form to transit staff and transit customers. The World Bank has participated in the financing of several ITS systems in China. Given the complexity of these projects and their potential for dramatic transformation of transit operating agencies, it is worthwhile to provide some guidance to senior staff from transit systems contemplating ITS projects as well as decision-makers external to the transit operating organizations The World Bank commissioned a series of three papers to assist in this effort. This first paper is a description of the key ITS applications for transit operations and where they are most beneficial. This second paper reviews a number of previous installations and reports on lessons learned, both positive and negative, in the hope of maximizing the effectiveness of technology in improving transit services. The third is a set of Terms of Reference (TOR's) for professional services associated with ITS project management to assist in project implementation these papers focus more on the organizational and planning issues associated with ITS. This guidance is primarily directed to bus transit operators, including those with bus rapid transit (BRT) services. However, the sections on fare collection and traffic signal priority may have some application to streetcar or light rail transit. Vehicle location on such systems is usually accomplished by a signal system used to control switching between tracks. This note serves as an introduction to the topic of ITS for transit. In it, we introduce the various ITS technologies, identify their benefits, and the range of applications where their use is most appropriate. The interaction among technologies in providing information useful to transit system management is also discussed. Of equal importance, we have found that successful implementation of ITS depends not only on the technology but also on the institutional environment in which they are implemented. Since the introduction of technology fundamentally changes the nature of traditional managerial and staff processes, organizations which are able to embrace change and alter their methods of doing business will be more likely to fully benefit from these installations. Accordingly, this paper discusses some of the institutional and organizational factors associated with ITS implementation. From the outset, this note does not advocate for the implementation of specific ITS technologies.